2017
DOI: 10.5812/ijcm.5700
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of HER2/neu Expression in Colorectal Cancer and its Relation to other Clinicopathological Criteria and Prognostic Factors

Abstract: Background: Human epidermal growth factor receptor 2 (HER2) overexpression and amplification have been studied as a therapeutic and prognostic target in a number of tumors although conflicting data exist about the incidence and clinical consequence of HER2/neu status in the patients with colorectal cancer. The aim of the present study was to evaluate the immunohistochemical expression of HER2/neu and its relationship with clinicopathological parameters and prognostic factors. Methods: This study involved 50 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
2
6
0
1
Order By: Relevance
“…In agreement with Song et al, (2014), Shabbir et al, (2016) and Sayadnejad et al, (2017) we did not find a significant link between HER2 expression and tumor stage or lymph node metastasis (TN stage). On the contrary, Elwy et al, (2012) and Heppner et al, (2014) reported a significant association with higher stages and positive nodal status.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with Song et al, (2014), Shabbir et al, (2016) and Sayadnejad et al, (2017) we did not find a significant link between HER2 expression and tumor stage or lymph node metastasis (TN stage). On the contrary, Elwy et al, (2012) and Heppner et al, (2014) reported a significant association with higher stages and positive nodal status.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to grade of differentiation in CRC cases, 4/6 of the positive and equivocal tumors were of low grade and exhibit mainly strong cytoplasmic/membranous expression, however no significant relationship was observed between CRC grades and HER2 pattern, which is consistent with several studies (Elwy et al, 2012;Pappas et al, 2013;Sayadnejad et al, 2017). However, several other studies reported the contrary.…”
Section: Discussionsupporting
confidence: 86%
“…did not find any significant correlation between the stage of tumors and the expression of HER2/neu [35], but Shabbir et al find such a correlation [33].…”
Section:  Discussionmentioning
confidence: 92%
“…Along the time, there were controversies about the levels of HER2/neu overexpression in patients with CRC. There are articles showing strong positivity (range: 30-83%) in primary CRC, but also some others who found only 1.6% of their 1645 cases to be HER2/neu positive [33][34][35][36]. There are some studies reporting a worse prognosis for HER2/neu positive CRC patients [37,38].…”
Section:  Discussionmentioning
confidence: 99%
“…University 2020;7(3 (11). Benzer şekilde Sayadnejad ve arkadaşları 50 olguluk çalışmalarında, yaş, tümör boyutu, cinsiyet, lokasyon, derece ve evre ile HER-2/neu ekspresyonu arasında anlamlı ilişki saptamamışlardır (13). Priyanka ve arkadaşları ise çalışmalarına dahil ettikleri 25 kolorektal kanserli olgunun tamamında HER-2/neu ekspresyonunu negatif saptamışlardır (14).…”
Section: Discussionunclassified